Label-free live-cell imaging with interferometric scattering microscopy: Confocal imaging and high-speed 3D single particle tracking - Küppers, Michelle; Kashkanova, Anna; Lühr, Jennifer; Albrecht, David; Schambony, Alexandra; Sandoghdar, Vahid (Optics InfoBase Conference Papers, 2020)
The combination of interferometric scattering microscopy (iSCAT) in wide-field and confocal detection reveals new prospects for the label-free visualization of subcellular processes and tracking of nanoscopic matter such as viruses, vesicles and lipid droplets.
CRIS-Team Scopus Importer:2020-10-02